2020
DOI: 10.1101/2020.09.01.20186320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of attitude among infertile couples about continuing assisted reproductive technologies therapy during novel coronavirus outbreak

Abstract: Study question: Does the fear of the coronavirus disease 2019 (COVID-19) pandemic reduce the desire of infertile couples to continue treatment? Summary answer: Most of the participants in this study wanted to continue treatment. What is known already: The effect of the prevalence of infectious diseases including the Zika virus on the attitude of infertile couples has been studied in very few studies. However, the effect of the outbreak of COVID-19 on the attitude of infertile couples has not been investigated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…So that women who were well aware of COVID 19, this decrease in desire and interest was observed in them less. [ 32 ] Furthermore, to prevent the spread of coronavirus, childbirth preparation classes, which have played an important role in raise awareness and reducing the fears and anxieties of pregnant mothers, are not held. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So that women who were well aware of COVID 19, this decrease in desire and interest was observed in them less. [ 32 ] Furthermore, to prevent the spread of coronavirus, childbirth preparation classes, which have played an important role in raise awareness and reducing the fears and anxieties of pregnant mothers, are not held. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 30 ] On the other hand, studies have shown that depression in men reduces the volume and quality of sperm, which exacerbates the problems of infertile couples. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, with mitigation strategies that have worked in several areas and the presence of additional data, as well as resistance to this policy, infertility therapy has resumed. ASRM, ESHRE, and International Federation of Fertility Societies have come asserted the importance of serial reproductive care during the COVID-19 pandemic [20], [23], [24], [25].…”
Section: Assisted Reproductive Technology During the Covid-19 Pandemicmentioning
confidence: 99%